Mechanism for Issuance of PEB (Goods Export Notification) with CEISA 4.0 Customs at PT. Kemasindo Cepat Medan - Aidil Patori; Yursal Yursal; Netty Kesuma (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The writing of this paper aims to find out more closely how the mechanism for issuing PEB (Notification of Export of Goods) with CEISA 4.0 Customs Excise at PT. Kemasindo Cepat Medan. BC 3.0 or PEB (Goods Export Notification) is a customs document used for the implementation of the export of goods by the exporter or his proxy PPJK (Customs Service Management Entrepreneur) to Customs made with CEISA 4.0 issued by Customs. The mechanism for issuing PEB using CEISA 4.0 Customs is the focus of this research. This study aims to find out the documents prepared, obstacles that occur during the work of B.C 3.0 using CEISA 4.0, procedures and obstacles that occur when completing PEB using CEISA 4.0. In the BC solution. 3.0 itself has several related parties, namely the exporter who informs his proxy, namely PPJK, that there will be goods that want to be exported. And after the goods are finished stuffed or loaded into containers, the exporter submits the documents as a condition for the issuance of PEB and the Customs checks the documents and approves the issuance of BC.3.0 or PEB through the CEISA 4.0 system. The data used in this study are primary data obtained through direct interviews with the company and secondary data obtained from books in the library and other reading sources related to the subject matter taken.